Corrosion Inhibition Efficiencies of Polymethacrylic Acid and Substituted Polymethacrylic Acid on Aluminium in 0.3M NaOH. (11th October 2021) - Devakumar, J.; Ramesh, V.; Suresh, P.; Anto Mariya Jeraldine, P.; Amaladass, P.; Santhi, R. Jaya
Abstract : Polymethacrylic acid (PMAA) and substituted polymethacrylic acid (PMAA/HQ) with para dihydroxy benzene (HQ) were synthesized via free radical polymerization and they were characterized using UV–vis, FT- IR, XRD spectral studies. The UV–vis spectrum of both PMAA and PMAA/HQ shows transitions due to π → π * at 218 and 306 nm respectively. The XRD analysis of PMAA shows semicrystalline, and the substituted PMAA shows amorphous. The morphology of the polymers determined from the SEM analysis exhibits fractured surface and cluster-like arrangement. The CV studies of PMAA/HQ and pristine HQ show that the redox behavior of HQ has changed in PMAA/HQ due to the polymeric effect. The corrosion inhibition efficiency of the resulting polymer was studied on aluminium in 0.3 M NaOH solution using weight loss, potentiodynamic polarization, and electrochemical impedance spectroscopic techniques, and their results were compared. The adsorption of synthesized polymer shows that the inhibition of aluminium in 0.3 M NaOH has been influenced by Langmuir adsorption isotherm. The anticorrosion and adsorption studies show that the corrosion inhibition potency of PMAA/HQ is more significant than PMAA.